S04-4 Tracking participants in the Jackpot.fit program and progress in dissemination of the Austrian sport promotion initiative. (29th August 2022) - Novak, Bernhard; Großschädl, Lena; Lackinger, Christian; Ruf, Wolfgang; Strehn, Albert; Titze, Sylvia
Abstract: Background: In 2015 a co-operation between the social insurance and the organized sport has been established in order to install Jackpot.fit, a standardized sports club based program, initially in 8 regions in Styria, a federal state of Austria. Inactive adults receive information about the long-term exercise program during a 3-week residential stay in a health resort. We aim to investigate who attends Jackpot.fit, the adherence to the program in 2019 as well as the progress of dissemination of Jackpot.fit since 2016. Methods: Participantś personal data were collected by telephone at the registration. Instructors documented the participants' attendance each single session with a standardized form. The number of participating regions as well as courses within the regions were monitored by the evaluator. Results: Between 2016 and 2019 2624 people (70.8% female; age: M = 57.1, SD = 9.1 years; BMI = 25.8, SD = 4.3 kg/m 2 ) registered for Jackpot.fit and 84.3% (n = 2212) attended as participants in at least one session. Between September and December 2019, 824 people registered for the courses with an adherence rate as follows: 291 (35.3%) visited 75% or more, 200 (24.3%) between 50% and 74.9% and 232 (28.2%) less than 49.9% of all 638 provided sessions. 101 (12.3%) registered but never attended once. The number of regions rose from 8 in 2016 to 28 in 2019 and the number of courses from 25 to 55 over the same period. Conclusions: According to the total number of participants, regions, and courses the dissemination moves forward. Further strategies to improve adherence must be developed. Acknowledgement: The project is supported by the Gesundheitsfonds Steiermark and the Bundessport Förderungsfonds.